Low Backache in Veiled Multipara Women: Prevalence and Response to Treatment - Khan, Muhammad Nadim Akbar; Saleem, M (International Journal of Pathology, 2018)
Background: The deficiency of vitamin D is unexpected in a tropical country like Pakistan, as there is abundantsunlight available. Vitamin D deficiency leading to hypocalcaemia and low backache is common in veiled multiparain northern areas of Pakistan. We designed a study to see the prevalence of low backache in these areas andtheir response to a cost effective treatment.Objective: To determine the prevalence and etiology of low backache in completely veiled multipara women ofnorthern areas of Pakistan and its response to a cost effective treatment.Design: Prospective interventional study.Setting: The Pain management team of Anesthesia and Obstetrics and Gynecology Departments of RailwayTeaching Hospital Rawalpindi along with other hospital Staff surveyed the earthquake affected Northern Areasof Pakistan.Duration of study: May 2008 to April 2009.Subjects and methods: 160 completely veiled multipara women, of northern areas of Pakistan; aged 20-45years, suffering from low backache were included in the study. A questionnaire was used to investigate clinicalcharacteristics, parity, exposure to sunlight, breast feeding, whether or not they wore the veil and menopause.The intensity of pain was measured by using Visual Analogue Scale (VAS). X- Rays lumbosacral spine AP andLateral view were done. We divided them into two groups with 80 women in each group. Group A was subjectedto cost effective treatment and counselling. Group B was used as control, and they were not treated or counselled.Group A responded miraculously to simple and cost effective empirical treatment including calcium, vitamin D,counselling about diet, exposure to sun and an active lifestyle. The intensity of low backache was again measuredat the end of six months by the same VAS. The pain of group A women were dramatically relieved but Group Bshowed little or no improvement in their symptoms. The results were statistically significant.Conclusions: In spite of abundant sunlight, healthy individuals in Northern areas of Pakistan are vitamin D deficientwhich ultimately leads to hypocalcaemia and osteoporosis. Healthy diet, change in life style like sunlightexposure and cost effective treatment can significantly reduce the complaints of low backache